(untitled) - Lesikar, Raymond V. (Boston, 2005)
Lesikar and Flatley's, Basic Business Communication (BBC): Skills for Empowering the Internet Generation, has long been known as a solid introductory business communication book that gets to the writing skills sooner than most other texts and gives students true 'how-to' skills in all areas of business communication. It has solid examples, and is both consumer-and service-oriented. Its strength has also been its use of margin notes, cartoons and photos that relate to the concepts and use of cases. Recent editions have established BBC as truly cutting edge; it was the first text in the market with PowerPoint as part of its package, the first to have an online chapter, and with the 9th Edition is now the first to offer writing tips and templates for PDAs (personal digital assistants).).
Keywords: English language,Business communication.,Ngôn ngữ tiếng Anh,Giao tiếp trong kinh doanh; Business English.,Tiếng Anh thương mại